2009
DOI: 10.2340/00015555-0729
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Features and Costs of Herpes Zoster in Taiwan: a National Study 2000 to 2006

Abstract: To analyse the epidemiological characteristics and related costs of herpes zoster in Taiwan, a nationally representative cohort of 1,000,000 individuals from the National Health Insurance register was followed up from 2000 to 2006 and their claims data analysed. Overall, 34,280 patients were diagnosed with zoster (incidence 4.89/1000 person-years) and 2944 patients (8.6%) developed post-herpetic neuralgia 3 months after the start of the zoster rash (incidence 0.42/1000 person-years). People with older age, dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
120
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(134 citation statements)
references
References 23 publications
7
120
1
6
Order By: Relevance
“…Previous studies showed that the higher-risk groups for herpes or post-herpetic neuralgia are those aged ≥60 years with diabetes, leukemia/lymphoma, renal failure, SLE, and transplant recipients [7,8,9,26,27]. Age is recognized as an important risk factor for herpes zoster [2,28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the higher-risk groups for herpes or post-herpetic neuralgia are those aged ≥60 years with diabetes, leukemia/lymphoma, renal failure, SLE, and transplant recipients [7,8,9,26,27]. Age is recognized as an important risk factor for herpes zoster [2,28].…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, the National Health Insurance (NHI) programme covers most of the population, and most medical institutions (91%) are contracted to the Bureau of NHL The National Health Insurance Research Database (NHIRD), one ofthe largest insurance databases in the world, includes all the claims from ambulatory care and inpatient care and provides valuable information for many epidemiological studies (16)(17)(18)(19). The aims of our study were to determine the overall prevalence of AD, AR and asthma in the general population, and to determine the relationships between these atopic diseases.…”
mentioning
confidence: 99%
“…Established risk factors for herpes zoster include older age, chronic kidney disease, malignant disease and immunocompromised conditions (e.g., those experienced by patients with AIDS, transplant recipients, and those taking immunosuppressive medication because of autoimmune diseases). [1][2][3][4][5] Herpes zoster occurs more frequently among patients with cancer than among those without cancer; 6,7 however the relation between herpes zoster and risk of subsequent cancer is not well established.…”
mentioning
confidence: 99%